2016
DOI: 10.1002/anie.201609601
|View full text |Cite
|
Sign up to set email alerts
|

Dibora[2]ferrocenophane: A Carbene‐Stabilized Diborene in a Strained cis‐Configuration

Abstract: Metallocenes with bridged cyclopentadienyl ligands, commonly named ansa metallocenes or metallocenophanes, have emerged as a class of organometallic compounds with an exceptionally wide and diverse range of applications.[1] Among other applications, ansa metallocenes are employed as catalyst precursors in the industrial production of polyolefins [2] and as monomers for ring-opening polymerization to form functional metallopolymers.[3] Their versatility and usefulness stems largely from the fact that their phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
34
0
9

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 55 publications
(85 reference statements)
4
34
0
9
Order By: Relevance
“…[2b, 8] The chemistry of strained sandwich compounds still yieldss urprising results as it can be exemplified with two recent highlights in this area, the FCP D and the nickelocenophane E (Figure 1). While the carbene-stabilized compound D exhibits an unusual bonding pattern, [9] species E is the first strained sandwichcompound revealing reversible ROP. [10] In addition to their application as monomers, phospha[1]ferrocenophanes are interestingp hosphines and can coordinate as monodentate ligandst ot ransition metals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2b, 8] The chemistry of strained sandwich compounds still yieldss urprising results as it can be exemplified with two recent highlights in this area, the FCP D and the nickelocenophane E (Figure 1). While the carbene-stabilized compound D exhibits an unusual bonding pattern, [9] species E is the first strained sandwichcompound revealing reversible ROP. [10] In addition to their application as monomers, phospha[1]ferrocenophanes are interestingp hosphines and can coordinate as monodentate ligandst ot ransition metals.…”
mentioning
confidence: 99%
“…[4] However,t he exploration into FCPs already began a few years after the discoveryo ff errocene, [5] with the first published derivative being ac arbon-bridged [3]FCP. While the carbene-stabilized compound D exhibits an unusual bonding pattern, [9] species E is the first strained sandwichcompound revealing reversible ROP. [2b, 8] The chemistry of strained sandwich compounds still yieldss urprising results as it can be exemplified with two recent highlights in this area, the FCP D and the nickelocenophane E (Figure 1).…”
mentioning
confidence: 99%
“…Cyclic voltammetry studies on THF solutions of compounds 5a and 5b (see Supporting Information) revealed oxidation waves;t he oxidation of 5a occurs at À1.19 V( all values vs.F c/Fc + ,F c = [(h-C 5 H 5 ) 2 Fe]), indicating that it is significantly more difficult to oxidise than previously studied NHC-stabilised diborenes (E 1/2 = À1.53 to À1.56 V), [16,17] whereas the oxidation wave of 5b is found at À0.80 V, av alue surpassed only by ad iborene stabilised by the relatively poor donor bis(diphenylphosphino)methane (E 1/2 = À0.51 V) TheHOMO energy is thus markedly affected by the thienyl substituent. Thep resence of the BMes 2 and B F Mes 2 groups also allows the species to be reduced; 5a displays ar eduction wave at À2.60 V, whereas for 5b this occurs at À1.73 V, showing the profound effect of fluorination of the aryl substituents.Indeed, the similarity of these values to the reduction potentials of related B F Mes 2 -a nd BMes 2 -substituted compounds,4 -tBuC 6 H 4 B F Mes 2 (E 1/2 = À1.63 V), 4-Ph 2 NC 6 H 4 B F Mes 2 (E 1/2 = À1.66 V) and 4-Ph 2 NC 6 H 4 BMes 2 (E 1/2 = À2.60 V), [10b] indicates that the effect of the donor on the reduction potential is relatively small.…”
mentioning
confidence: 99%
“…Die Oxidation von 5a erfolgt bei E 1/2 = À1.19 V (alle Werte vs.Fc/Fc + ), was darauf hindeutet, dass es sich im Vergleich mit bereits untersuchten NHC-stabilisierten Diborenen (E 1/2 = À1.53 bis À1.56 V) [16,17] wesentlich schwieriger oxidieren lässt. Die Oxidation von 5a erfolgt bei E 1/2 = À1.19 V (alle Werte vs.Fc/Fc + ), was darauf hindeutet, dass es sich im Vergleich mit bereits untersuchten NHC-stabilisierten Diborenen (E 1/2 = À1.53 bis À1.56 V) [16,17] wesentlich schwieriger oxidieren lässt.…”
unclassified